Out in the cold - Warren, Andrian; Jones, Laurie; Attenborough, David, 1926-. (London : BBC Enterprises, 1981)
Animals face difficulties when their food is smoothered by a blanket of snow or set solid ice. All over our planet animals and plants have proved themselves to be adaptable to cold than man and sometimes the results are weird and unexpected
Backup available VHS 1/2 in.
Keywords: Cold adaptation; Cold -- Physiological effect